Research on the Promotion Path of Intangible Cultural Heritage in Primary School Campus Based on the AGIL Model (Journal of Education and Development, 2024)
With the introduction of policies to promote intangible cultural heritage into schools, intangible cultural heritage plays an increasingly important role in primary education. However, the implementation of the intangible cultural heritage policy in primary schools is mostly formalized, which leads to many problems in the